ANALYSIS OF THE EFFECT OF PRESSURE AND AIR FLOW RATE ON THE PURITY OF NITROGEN GAS PRODUCTS PRODUCED BY THE PRESSURE SWING ADSORPTION (PSA) METHOD AT PT. ARUN GAS PERTA - Jalaluddin, J; Yunus, M; Elfiana, E (Jurnal Sains dan Teknologi Reaksi, 2024)
ABSTRACTNitrogen is a basic compound in the chemical industry. Nitrogen is an inert gas compound so it is suitable for various applications covering various aspects of manufacturing, processing, handling and shipping chemicals. The aim of this research is to analyze the influence of impurities, pressure and air flow rate on the purity of nitrogen gas products produced using the Pressure Swing Adsorption (PSA) method, then carry out a comparison or simulation of actual field data with Aspen Adsorption V.10. The research method used is descriptive qualitative, the data in this research is field operational data and data collection techniques are carried out periodically through data log sheets. From the research results, it was found that Purity in October to November 2023 on October 5 and 27 was 99.98%, with a flow of 52.2 Nm3/h, while for November there was 98.01% (purity) with flow 105.0 Nm3/h. And after carrying out simulations using Aspen Adsorption V.10 and varying the input data, Purity was obtained at 99.98%, 99.97%, 99.91% with a flow of 100 Nm3/h, 150 Nm3/h, 200 Nm3/h or 0, 4461 kmol/s, 0.6692 kmol/s, 0.8992 kmol/s in Aspen Adsorption V.10 applications.Keywords: Nitrogen, Pressure Swing Adsorption (PSA), Aspen Adsorption, Carbon Molecular Sieve (CMS)